H2‐Directing Strategy on In Situ Synthesis of Co‐MoS2 with Highly Expanded Interlayer for Elegant HER Activity and its Mechanism. Issue 20 (6th April 2020) - Jin, Qiu; Liu, Ning; Dai, Chengna; Xu, Ruinian; Wu, Bin; Yu, Gangqiang; Chen, Biaohua; Du, Yanze
Abstract: MoS2 has drawn great attention as a promising Pt‐substituting catalyst for the hydrogen evolution reaction (HER). This work utilizes H2 as the structure directing agent (SDA) to in situ synthesize a range of Co‐MoS2 ‐ n ( n = 0, 0.5, 1.0, 1.4, 2.0) with expanded interlayer spacings ( d = 9.2 – 11.1 Å), which significantly boost their HER activities. The Co‐MoS2 ‐1.4 with an interlayer spacing of 10.3 Å presents an extremely low overpotential of 56 mV (at 10 mA cm −2 ) and a Tafel slope of 32 mV dec −1, which is superior than most reported MoS2 ‐based catalysts. Density function theory calculations are used to gain insights that i) the H2 can be dissociatively adsorbed on MoS2 and greatly affect the related surface free energy by regulating the interlayer spacing; ii) the expanded interlayer spacing can significantly decrease the absolute value of Δ G H, thereby leading to greatly promoted HER activity. Additionally, the large amounts of 1T phase (73.9–79.2%) and Co‐Mo‐S active sites (40.9–91.3%) also contribute to the enhanced HER activity of the synthesized samples. Overall, a simple new strategy for in situ synthesis of Co‐MoS2 with an expanded interlayer spacing is proposed, which sheds light on other 2D energy material designs. Abstract : This work utilizes H2 as the structure directing agent to successfully synthesizes a series of Co‐MoS2 with highly expanded interlayer spacings ( d = 9.2–11.1 Å), which significantly boost their hydrogen evolution reaction (HER) activities. Deep mechanistic insights into the directing mechanism of H2 and structure‐activity relationship between the as‐synthesized catalyst and the super high HER activity are unraveled by density functional theory.